Las enfermedades raras y los medicamentos huérfanos, su reconocimiento y protagonismo a lo largo del siglo XX - Bel Prieto, Elvira; Bonet Clols, Francesc (Debater a Europa, 2016)
The regulation of orphan drugs in the EU is implemented by the approval of the EC Regulation 141/2000. Nevertheless, up to its publication, there was a difficult way to go, a fact which had already become clear in the late eighteenth century through publications and letters in journals of scientific character. Thus, we considered analyzing the evolution of the denominations ’rare disease’ and ’orphan drug, their scope, and the problems which preceded the approval of the regulation; and furthermore, assessing the impact of the proposals on governmental actions and on the regulation which has been approved. http://dx.doi.org/10.14195/1647-6336_14_8